Optimization of the apolipoprotein B mRNA editing enzyme catalytic polypeptidelike-3G (APOBEC3G) gene to enhance its expression in Escherichia coli (Medical Journal of Indonesia, 2020)
BACKGROUND Apolipoprotein B mRNA editing enzyme catalytic polypeptide-like-3G (APOBEC3G) can abolish HIV infection by inducing lethal mutations in the HIV genome. The HIV protein virion infectivity factor (Vif) can interact with APOBEC3G protein and cause its degradation. Development of a method that can screen substances inhibiting the APOBEC3G-Vif interaction is necessary for identification of substances that potentially used in anti-HIV drug development. In order to increase expression of recombinant APOBEC3G protein that will be used in APOBEC3G-Vif interaction assay, we developed an optimized APOBEC3G gene for expression in Escherichia coli. METHODS The gene coding APOBEC3G was codon-optimized in accordance with prokaryotic codon using DNA 2.0 software to avoid bias codons that could inhibit its expression. The APOBEC3G gene was synthesized and sub-cloned into pQE80L plasmid vector. pQE80L containing APOBEC3G was screened by polymerase chain reaction, enzyme restriction, and sequencing to verify its DNA sequence. The recombinant APOBEC3G was expressed in E. coli under isopropyl-β-D-thiogalactoside (IPTG) induction and purified by using nickel-nitrilotriacetic acid (Ni-NTA) resin. RESULTS The synthetic gene coding APOBEC3G was successfully cloned into the pQE80L vector and could be expressed abundantly in E. coli BL21 in the presence of IPTG. CONCLUSIONS Recombinant APOBEC3G is robustly expressed in E. coli BL21, and the APOBEC3G protein could be purified by using Ni-NTA. The molecular weight of the recombinant APOBEC3G produced is smaller than the expected value. However, the protein is predicted to be able to interact with Vif because this interaction is determined by a specific domain located on the N-terminal of APOBEC3G.